2014
DOI: 10.1007/s40121-014-0025-y
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology of Pneumococcal Disease in a National Cohort of Older Adults

Abstract: IntroductionStreptococcus pneumoniae is a major cause of morbidity and mortality. We sought to describe the epidemiology of non-invasive and invasive pneumococcal disease in a national Veterans Affairs population within the United States.MethodsWe conducted a retrospective study in older patients (aged ≥50 years) with positive pneumococcal cultures from any site between 2002 and 2011. We described outpatient and inpatient pneumococcal disease incidence per 100,000 clinic visits/hospitalizations. Repeat culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 52 publications
4
29
0
1
Order By: Relevance
“…Risk factors for meningitis include: skipping vaccinations, age (most cases of viral meningitis occur in children younger than five years old and bacterial meningitis commonly affects people under 20), living in a community setting (college students living in dormitories, personnel on military bas-es, and children in boarding schools and child care facilities are at increased risk of meningococcal meningitis), and factors that may compromise patients' immune system including; AIDS, use of immunosuppressant drugs, and removal of the spleen (3-6). There are many reports about the epidemiology of meningitis and according to the community under study, age of cases and other risk factors, agents and clinical outcome are different (8)(9)(10)(11)(12)(13)(14)(15)(16)). …”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for meningitis include: skipping vaccinations, age (most cases of viral meningitis occur in children younger than five years old and bacterial meningitis commonly affects people under 20), living in a community setting (college students living in dormitories, personnel on military bas-es, and children in boarding schools and child care facilities are at increased risk of meningococcal meningitis), and factors that may compromise patients' immune system including; AIDS, use of immunosuppressant drugs, and removal of the spleen (3-6). There are many reports about the epidemiology of meningitis and according to the community under study, age of cases and other risk factors, agents and clinical outcome are different (8)(9)(10)(11)(12)(13)(14)(15)(16)). …”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Despite the established benefits of pneumococcal vaccination, multiple studies have identified that current pneumococcal vaccination rates are far below the Healthy People 2020 goals. 11,28 In 2013, the National Health Interview Survey indicated that approximately 67 million at-risk individuals in the U.S. have not received pneumococcal vaccination, placing them at an increased risk of worse outcomes and more severe pneumococcal infection. 5,29 This is concerning, as previous research has demonstrated that people with ACIP indications for pneumococcal vaccination are twice as likely to die as those without indications if they develop invasive pneumococcal disease.…”
Section: Discussionmentioning
confidence: 99%
“…The Veterans Affairs databases have been described previously. 11,12 An analytic database was created from numerous Veterans Affairs databases capturing patient care, including demographics, inpatient stays, outpatient visits, pharmacy dispensings and administrations, health factors, surgeries and procedures, laboratory and microbiology results, immunizations, and vital status.…”
Section: The Irb and The Research And Development Committee Of The Prmentioning
confidence: 99%
See 2 more Smart Citations